Junk raft : an ocean voyage and a rising tide of activism to fight plastic pollution - Eriksen, Marcus, 1967- (Beacon Press, 2017)
"An exciting account of an activist scientist's unorthodox fight in the growing movement against plastic marine pollution and of his expedition across the Pacific on a home-made "junk raft" Over the past several years, the news media has brought the "Great Pacific Garbage Patch"--The famous swirling gyre of plastic litter in the ocean--into the public consciousness. When Marcus Eriksen cofounded the 5 Gyres Institute with his wife, Anna, and set out to study marine pollution, they found that the reality is even more dire: instead of a stable mass of litter, they discovered that a "plastic smog" of microparticles permeates the world's oceans, defying simplistic clean-up efforts. What's more, these microplastics and their toxic chemistry have seeped into the food chain, threatening marine life and humans alike. Far from being a gloomy treatise on an environmental catastrophe, though, Junk Raft tells the exciting story of Eriksen's fight to raise awareness and solve the problem of plastic pollution, contributing to a fast-growing movement to stem the tide of trash. Eriksen writes of his voyage from Los Angeles to Hawaii aboard his homemade "junk raft," and along the way he recounts the successful efforts to fight corporate influence and demand that plastics producers take responsibility for a problem they've created. Eriksen provides concrete, actionable solutions and an empowering message: it's up to bold, brash, unapologetically activist "citizen scientists" to challenge the status quo for the sake of the planet"--